Chemical Biology & Biochemistry Laboratory Using Genetic Code Expansion Manual - Mehl, Ryan; van Zee, Kari; Kean, Kelsey; Open Textbook Library (Open Textbook Library, 2019)
Chemical Biology & Biochemistry Laboratory Using Genetic Code Expansion Manual
1. Background -- 2. Overview of Laboratory Responsibilities Tentative Schedule -- 3. Objectives for Week 1 -- 4. Concepts for Choosing and Expressing Mutants -- 5. Objectives for Week 2 -- 6. Concepts for Protein Expression -- 7. Methods for Protein Expression -- 8. Concepts for SDS-PAGE -- 9. Methods for SDS-PAGE -- 10. Objectives for Week 3 -- 11. Concepts for Protein Purification and Desalting -- 12. Methods for Protein Purification and Desalting -- 13. Microfluidizer Lysis Method -- 14. Objectives for Week 4 -- 15. Methods for Protein Standard Curves and SDS-PAGE -- 16. Objectives for Weeks 5-9 -- 17. Concepts for Enzyme Assays -- 18. Methods for Enzyme Assays
In English.
Description based on print resource
Keywords: Chemistry -- Textbooks